Usefulness of rebiopsy in the case of mesangial pathology - Żurawski, Jakub; Talarska, Patrycja; Salwa-Żurawska, Wiesława; Iwanik, Katarzyna; Bulak, Joanna; Woźniak, Aldona (Polish Journal of Pathology, 2021)
Immunologically different types of glomerulopathies show varied symptoms and clinical courses. Unlike in lupus nephritis, repeated biopsy is rarely performed in cases of mesangial glomerulonephritis. We reviewed 200 cases wherein rebiopsy was performed in patients with diagnosed mesangial glomerular pathology over a 30-year period and analyzed the symptoms follow-up in these cases. Further, we evaluated the morphological changes between the first and final biopsies to identify cases of histological progression and histological remission and examined the correlation between such changes and clinical symptoms. The time between the first and last biopsies ranged from 7 months to 35 years. The most common for the initial biopsy was nephrotic syndrome, followed by non-nephrotic proteinuria; other symptoms occurred rarely. Histological progression occurred at various stages of observation, ranging from within a few months to after several years. Histological progression and remission were detected in 118 and 3 patients, respectively, whereas there was no difference in morphological findings between the first and last biopsies in 79 patients. Rebiopsy is useful in patients who do not respond adequately to treatment, and especially in those with increased clinical symptoms. Moreover, electron microscopic examination is necessary to discover early signs of histological progression.